1998
DOI: 10.1037/0022-3514.74.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Implicit theories of relationships: Assessment and prediction of romantic relationship initiation, coping, and longevity.

Abstract: Belief in romantic destiny holds that potential relationship partners are either meant for each other or they are not. As hypothesized, a longitudinal study of romantic relationships revealed that the relation between initial satisfaction and relationship longevity was stronger for those who believe in romantic destiny. In addition, belief in destiny was associated with avoidance coping strategies in dealing with relationship stressors, and with taking more responsibility for ending the relationship. Belief in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
320
1
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(342 citation statements)
references
References 66 publications
(85 reference statements)
11
320
1
10
Order By: Relevance
“…Results from both studies revealed that participants experiencing state attachment anxiety became less forgiving as the strength of their destiny beliefs increased, whereas those experiencing state attachment security exhibited no association (or, if anything, a positive association) of destiny beliefs with forgiveness tendencies (see Figures 1 through 3). These effects emerged (see Study 1) with an experimental manipulation of attachment anxiety (vs. security) and remained significant (or nearly significant; see Study 2) after controlling for trait attachment anxiety, trait attachment avoidance, trait forgiveness tendencies, self-deception, impression management, time since the offense, offense severity, relationship commitment, relationship closeness, and the Destiny Beliefs ϫ Relationship Closeness interaction effect that had been previously identified (Knee, 1998) as a predictor of relationship outcomes. The longitudinal effect also controlled for earlier forgiveness tendencies.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Results from both studies revealed that participants experiencing state attachment anxiety became less forgiving as the strength of their destiny beliefs increased, whereas those experiencing state attachment security exhibited no association (or, if anything, a positive association) of destiny beliefs with forgiveness tendencies (see Figures 1 through 3). These effects emerged (see Study 1) with an experimental manipulation of attachment anxiety (vs. security) and remained significant (or nearly significant; see Study 2) after controlling for trait attachment anxiety, trait attachment avoidance, trait forgiveness tendencies, self-deception, impression management, time since the offense, offense severity, relationship commitment, relationship closeness, and the Destiny Beliefs ϫ Relationship Closeness interaction effect that had been previously identified (Knee, 1998) as a predictor of relationship outcomes. The longitudinal effect also controlled for earlier forgiveness tendencies.…”
Section: Discussionmentioning
confidence: 72%
“…These mediational results provide strong support for this conceptual analysis. Toward the goal of garnering additional support for it, we established discriminant validity by replicating the mediational analyses, this time substituting in relationship closeness (Knee, 1998) for state attachment anxiety. Given that relationship closeness is not hypothesized to highlight trust-relevant issues in the way state attachment anxiety does, we anticipated that trust would not significantly mediate the Destiny Beliefs ϫ Relationship Closeness interaction effect on delayed forgiveness.…”
Section: Mediation By Trust?mentioning
confidence: 99%
“…Research in implicit theories of relationships show that people either have destiny beliefs or growth beliefs (Knee, 1998). Research has shown that these beliefs are conceptually distinct from each other (Knee et al, 2001).…”
Section: Implicit Theories Of Relationship and Gift-givingmentioning
confidence: 99%
“…Nonetheless, research has not considered whether consumers' gift-giving behavior is driven by their belief of what constitutes a good relationship. Research in social psychology shows that people have two different beliefs about the nature of relationships known as the implicit theories of relationship which are either growth or destiny beliefs (Knee, 1998). People who have destiny beliefs hold that relationships are destined and assume that potential partners are meant either for each other or not.…”
Section: Introductionmentioning
confidence: 99%
“…Given the focus upon relatedness and belongingness as key markers of a life well-lived, the role of implicit theories in this life domain holds significant import for a science of wellbeing. Knee (1998) initiated the study of implicit theories regarding romantic relationships more than 15 years ago. In their reviews of this literature, Knee, Patrick, and Lonsbary (2003) and Knee and Petty (2013) characterise growth beliefs as a mindset wherein relationships can be maintained and conflicts overcome through effort and problem-solving, whereas they characterise destiny beliefs as a mindset wherein relationships either are or are not "meant to be" (see also the work-itout and soulmate beliefs identified by Franiuk, Cohen, & Pomerantz, 2002).…”
Section: Relationshipsmentioning
confidence: 99%